An Analising EFLTeacher’s Politeness Strategies in Classroom Interaction: Politeness Strategies - Rifai, Ahmad (Foreign Language Instruction Probe, 2022)
ABSTRACT The purpose of this study is to investigate at how politeness strategies are used in EFL classroom interactions in a senior high school. This study employed a descriptive qualitative research approach to investigate the teacher and student politeness strategies in their interactions. An English teacher and 35 students took part in this research. This data in this research were taken from the form of utterances containing politeness strategies. The data was provided via a video-recorded 90-minute English class. There were six extracts with three politeness strategies: positive politeness strategy, negative politeness strategy, and bald-on-record method, according to the findings. The teacher was in charge of the exchanges. Furthermore, various characteristics such as age difference, institutional position, authority, and social distance affected politeness strategies used in classroom interactions. Key Words: classroom interaction, politeness, politeness strategy